Elevated Temperatures Impose Transcriptional Constraints and Elicit Intraspecific Differences Between Coffee Genotypes - de Oliveira, Raphael Ricon; Ribeiro, Thales Henrique Cherubino; Cardon, Carlos Henrique; Fedenia, Lauren; Maia, Vinicius Andrade; Barbosa, Barbara Castanheira Ferrara; Caldeira, Cecílio Frois; Klein, Patricia E.; Chalfun-Junior, Antonio (Frontiers in Plant Science, 2020)
The projected impact of global warming on coffee production may require the heat-adapted genotypes in the next decades. To identify cellular strategies in response to warmer temperatures, we compared the effect of elevated temperature on two commercial Coffea arabica L. genotypes exploring leaf physiology, transcriptome and carbohydrate/protein composition. Growth temperatures were 23/19°C (day/night), as optimal condition (OpT), and 30/26°C (day/night) as a possible warmer scenario (WaT). The cv. Acauã showed lower levels of leaf temperature under both conditions compared to cv. Catuaí, whereas slightly or no differences for other leaf physiological parameters. Therefore, to explore temperature responsive pathways the leaf transcriptome was examined using RNAseq. Genotypes showed a marked number of differentially-expressed genes (DEGs) under OpT, however DEGs strongly decrease in both at WaT condition indicating a transcriptional constraint. DEGs responsive to WaT revealed shared and genotype-specific genes mostly related to carbohydrate metabolism. Under OpT, leaf starch content was greater in cv. Acauã and, as WaT temperature was imposed, the leaf soluble sugar did not change in contrast to cv. Catuaí, although the levels of leaf starch, sucrose, and leaf protein decreased in both genotypes. These findings revealed intraspecific differences in the underlying transcriptional and metabolic interconnected pathways responsive to warmer temperatures, which is potentially linked to thermotolerance, and thus may be useful as biomarkers in breeding for a changing climate.